Natural history of liver fluke infection underpins epidemiological patterns of biliary cancer - Thomas Crellen; Francesca Vita; Chiara Braconi; Paiboon Sithithaworn; T. Déirdre Hollingsworth (Proceedings of the National Academy of Sciences, 2025)
Pathogens are major drivers of cancer globally and the processes of infection and carcinogenesis unfold over decades making them difficult to observe in human or natural populations. We investigate these hidden dynamics for the foodborne trematode Opisthorchis viverrini , which is a primary cause of biliary cancer (cholangiocarcinoma) and infects 12 million people in Southeast Asia. In tumors from patients exposed to O. viverrini , we find that the earliest chromosomal amplifications carrying driver genes occurred at 30 y old on average, two to four decades before cancer diagnosis, and disproportionately contain TP53 , PTEN and FGFR2 genes. We then fitted transmission models to parasitological data from Thailand spanning 27 y ( n = 11,517) finding that, for people born between 1960 and 1989, first exposure occurred at two years old and by 30 y individuals had been cumulatively infected with a median of 72 worms. Trematodes are long-lived and our analysis quantifies the average lifespan of O. viverrini as 13 y (90% credible interval [CrI] 7 to 26 y) within human hosts. The lifetime probability of diagnosis with cholangiocarcinoma is 4.9% (90% CrI 4.7 to 5.0%) given prior exposure to O. viverrini , which is fourteen-fold higher than in populations nonendemic for the parasite. We find strong evidence for a dramatic decline in parasite transmission from 1990 onward in Thailand, suggesting that the incidence of cholangiocarcinoma will decline over the coming decades. Our study demonstrates how pathogen exposure drives patterns of cancer within a population and provides evidence for public health and therapeutic interventions.